2021
DOI: 10.3390/mi12111283
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Aptamer-Based Sensor for Detection of Mercury(II) and Lead(II) Ions in Water

Abstract: Heavy metal contaminants have serious consequences for the environment and human health. Consequently, effective methods for detecting their presence, particularly in water and food, are urgently required. Accordingly, the present study proposes a sensor capable of detecting mercury Hg(II) and lead Pb(II) ions simultaneously, using graphene oxide (GO) as a quenching agent and an aptamer solution as a reagent. In the proposed device, the aptamer sequences are labeled by FAM and HEX fluorescent dyes, respectivel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Micromilling and 3D printed devices were explored for heavy metal detection (Santangelo et al, 2019;Huang et al, 2021) and though these devices were successful experimentally and demonstrated enough accuracy to be used in the lab, the dependency on external pumping systems and trained personnel still limit their market potential. When it comes to processing samples with large volumes, injection molded devices have emerged as a major player.…”
Section: Discussionmentioning
confidence: 99%
“…Micromilling and 3D printed devices were explored for heavy metal detection (Santangelo et al, 2019;Huang et al, 2021) and though these devices were successful experimentally and demonstrated enough accuracy to be used in the lab, the dependency on external pumping systems and trained personnel still limit their market potential. When it comes to processing samples with large volumes, injection molded devices have emerged as a major player.…”
Section: Discussionmentioning
confidence: 99%
“…A microfluidic aptamer sensor capable of detecting Hg and Pb ions simultaneously was developed by Huang et al [85]. The GO was used as the quencher, and an octanoic acid solution was used as the reagent.…”
Section: Ion-like Substance Detectionmentioning
confidence: 99%
“…In the case of microfluidic devices integrated with biosensors and dedicated to metal ions detection, such an approach is still in its very initial stage; however, progress made for medical (biomarkers) application can be fully utilized. One such example is the device proposed by Huang, W.-H. et al [ 118 ]. The authors proposed a device capable of simultaneous detection of Hg 2+ and Pb 2+ ions ( Figure 31 ).…”
Section: Microfluidic Aptamer-based Sensors For Ions Detectionmentioning
confidence: 99%
“… ( A ) experimental setup; ( B ) Schematic integration of experimental setup; ( C , D ) exemplary result of simultaneous detection of Hg 2+ and Pb 2+ ions in two concentrations, 10 nM and 100 nM respectively [ 118 ]. …”
Section: Figurementioning
confidence: 99%